Sistem Rekrutmen Tenaga Pendidik dan Kependidikan pada Pendidikan Formal di Yayasan Pondok Pesantren Mukhtar Syafa'at Banyuwangi - Nurkafidz Nizam Fahmi; Ahmad Zahidin (Institut Agama Islam Darussalam Blokagung, 2020)
The objectives of this study were 1) to study the process of recruiting educators and education personnel in formal education at the Mukhtar Syafa'at Blokagung Islamic Boarding School, 2) to find out researchers and obstacles to the recruitment system for educators and education personnel in the formal education of the Mukhtar Syafa'at Islamic boarding school. blokagung. This type of research is quantitative descriptive using observation, interview instruments and documentation for data analysis techniques while the analysis uses miles and huberman. The results of the study included a) Teacher recruitment prioritizing santri and alumni of the Mukhtar Syafa'at Blokagung Islamic boarding school foundation, b) Educator and education recruitment was carried out centrally by the head of the education sector and the construction of the Mukhtar Syafa'at Blokagung Islamic boarding school foundation assisted by the foundation secretary, head of the field quality assurance and principal of each unit, c) Submission of non-permanent teacher decrees for 2 years as a test of teacher and employee loyalty.